2017
DOI: 10.3389/fpsyt.2017.00050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Alcohol, Smoking, and Substance Involvement Screening Test-Linked Brief Intervention on Harmful and Hazardous Alcohol Use in Nigerian Semirural Communities: A Non-Randomized Intervention Study

Abstract: ObjectiveTo determine the prevalence of alcohol consumption and the effectiveness of the alcohol, smoking, and substance involvement screening test (ASSIST)-linked brief intervention on hazardous and harmful alcohol use in semirural settings in Nigeria.MethodsIn this single arm non-randomized intervention study delivered by community health extension workers (CHEW), participants (N = 1,203), 15 years and older, recruited between October 2010 and April 2011 were assessed for prevalence of alcohol consumption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…While a previous study in Nigeria has highlighted the efficacy of community health extension worker delivered screening and ASSIST-linked intervention on problem alcohol use, it stands to be seen if such could be replicated for other substances apart from alcohol given that alcohol is a socially accepted drug of use and a more accommodating attitude is displayed towards its use. 33 This may be the subject of further research. Finally, this study did not include follow up to assess the impact of ASSIST-linked brief intervention on the beneficiaries; nor feedback from the referrals.…”
Section: Resultsmentioning
confidence: 99%
“…While a previous study in Nigeria has highlighted the efficacy of community health extension worker delivered screening and ASSIST-linked intervention on problem alcohol use, it stands to be seen if such could be replicated for other substances apart from alcohol given that alcohol is a socially accepted drug of use and a more accommodating attitude is displayed towards its use. 33 This may be the subject of further research. Finally, this study did not include follow up to assess the impact of ASSIST-linked brief intervention on the beneficiaries; nor feedback from the referrals.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, khat chewing and tobacco using behavior were defined as self-reported currently chewing of khat and practicing of smoked tobacco or smokeless tobacco products, respectively. Current alcohol users are defined as people who drink alcohol more than one day per week [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…After preliminary evaluation of included publications, we developed a categorization for interventions, as follows: psychotherapeutic, social, lifestyle/physical health, economic, and psychopharmacological interventions. About 10% of psychotherapeutic interventions utilized a singlesession intervention approach (14/144) (Stein et al, 1997;Igreja et al, 2004;Connolly and Sakai, 2011;Cubbins et al, 2012;Eller et al, 2013;Pengpid et al, 2013;Morojele et al, 2014;Lasebikan et al, 2017;De Fouchier and Kedia, 2018;Harder et al, 2020;Osborn et al, 2020;Akena et al, 2021;Wasil et al, 2021;Venturo-Conerly et al, 2022). A total of 10 studies quantitively assessed the effect of a single session intervention on MH or SU, of which eight studies indicated a statistically significant MH or SU reduction.…”
Section: Intervention Approach Categoriesmentioning
confidence: 99%
“…A total of 10 studies quantitively assessed the effect of a single session intervention on MH or SU, of which eight studies indicated a statistically significant MH or SU reduction. Notably, a self-help component, including distribution of manuals or leaflets about psychoeducation, self-care strategies, problem-solving steps, or a drinking diary, was present in 75% of the single-session interventions that showed such a reduction (6/8) (Connolly and Sakai, 2011;Eller et al, 2013;Pengpid et al, 2013;Lasebikan et al, 2017;De Fouchier and Kedia, 2018;Osborn et al, 2020).…”
Section: Intervention Approach Categoriesmentioning
confidence: 99%